Mechanism of Nanorod Formation by Wormlike Micelle-Assisted Assembly of Nanospheres - Chhatre, Advait; Duttagupta, Suvajeet; Thaokar, Rochish; Mehra, Anurag (Langmuir, 2015)
Hierarchical self-assembly is an elegant and energy-efficient bottom-up method for the structuring of complex materials. We demonstrate the synthesis of maghemite nanorods via directed self-assembly, assisted by wormlike micelles, under controlled shear. The experimental data are analyzed by formulating a “slithering snake” mechanism and simulating it on a cubic lattice, using a coarse-grained Monte Carlo framework. The influence of shear rate, precursor concentration, and length of Kuhn segment on the morphology of the nanorods is examined. Experiments indicate that the shear is necessary for the formation of nanorods, although diameter and length of the nanorods are insensitive to the shear rate, within the range of shear rates investigated. The model adequately captures the features of directional aggregation of particles, and the computed length and diameter correspond to the typical dimensions of the nanorods obtained experimentally. The protocol has considerable potential for producing nanorods of several materials simply by changing the precursors.